How Digital Hybridization Creates New Performance Practices: The Case of Alternate Virtuality Games (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
In this paper, we examine a new set of hybrid ludic practices utilizing cross-media narration that emerged with the rise of the Internet commonly called Alternate Reality Games. However, we propose to coin the term Alternate Virtuality Games (or AVG) as a way to distinguish these digital practices from their real-life counterpart. Viral online AVGs like This House Has People in It (Resnick, 2016) or Ben Drowned (Jadusable, 2010) are emblematic of a horizontal relationship between work and spectator, as well as performance outside of art institutions. The immersiveness of AVGs is unbound by the space and time of a specific happening, and is rather experienced by a multitude of agents at different times and places. This characteristic of being an extra-individual experience as well as being independent from institutions also places AVGs within liminal experiences such as studied by anthropologist Victor Turner.As such, we analyze these hybrid games as a mean for the 21st century spectator to overturn societal status quo through newfound agency. These performing agents get into a subjective state where they can experience and criticize our relationship to digital devices in a society of information and control, without being subjected to it.
Keywords: Alternate reality game; Liminality; Digital studies; Mediatic event; Subjectivation